Underworld justice in Imperial China and its continuing influence in Hong Kong - Kwok, D (2017)
This thesis explores the imagery of underworld justice, and its associated beliefs and practices, as they developed throughout Chinese imperial history. Certain elements of the Chinese imperial legal system, including judges and trials, and laws and codes, were borrowed by the Daoists and applied to their construct of the afterlife. Underworld justice beliefs and practices flourished throughout China‘s imperial past, and are still influential to some devotees in today‘s Hong Kong. Among the various questions that are explored, this thesis examines the place of underworld justice in the legal consciousness, or everyday law, of the devotees in contemporary Hong Kong. There are two dimensions to this thesis: historical and empirical. In the historical part, I trace the development of underworld justice beliefs and practices in imperial China. I analyse some of the characteristics and rituals of underworld justice, and relate them to the imperial laws and procedures upon which they were modelled. Such tracing allows us to discern the considerable overlap between the imperial legal system and underworld justice beliefs and practices. In the empirical part, I present data gathered at mainly three City God temples in Hong Kong. Such data involve conversations with Daoist and Buddhist priests, temple keepers and devotees. The data gathered not only shed light on the general state of City God veneration in contemporary Hong Kong, but also the influence of underworld justice on the devotees‘ understanding of law. The data reveal that the studied devotees regard underworld justice, which administers the law of karma, as superior to the state legal system. Hence, underworld justice is not considered as an informal dispute resolution process alternative to that of the state, but as a mechanism that can intervene in court cases, due to its being more authoritative.